2018
DOI: 10.48550/arxiv.1811.03797
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unstable entropies and Dimension Theory of Partially Hyperbolic Systems

Abstract: In this paper we define unstable topological entropy for any subsets (not necessarily compact or invariant) in partially hyperbolic systems as a Carathéodory dimension characteristic, motivated by the work of Bowen and Pesin etc. We then establish some basic results in dimension theory for Bowen unstable topological entropy, including an entropy distribution principle and a variational principle in general setting. As applications of this new concept, we study unstable topological entropy of saturated sets and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…In fact, the unstable metric entropy in [8] has root in the entropy introduced by Ledrappier and Young ( [11]), and is easier to apply. In [15], Tian and Wu generalize the above result with additional consideration of an arbitrary subset (not necessarily compact or invariant). In [9], Hu, Wu, and Zhu investigated the unstable topological pressure for additive potentials, and obtained a variational principle.…”
Section: Introductionmentioning
confidence: 72%
“…In fact, the unstable metric entropy in [8] has root in the entropy introduced by Ledrappier and Young ( [11]), and is easier to apply. In [15], Tian and Wu generalize the above result with additional consideration of an arbitrary subset (not necessarily compact or invariant). In [9], Hu, Wu, and Zhu investigated the unstable topological pressure for additive potentials, and obtained a variational principle.…”
Section: Introductionmentioning
confidence: 72%
“…They were introduced and studied in [5] by Hu, Hua, and Wu; moreover, they obtained the corresponding Shannon-McMillan-Breiman theorem, as well as the corresponding variational principle. In [12], Tian and Wu generalize the result above with additional consideration of an arbitrary subset (not necessarily compact or invariant). In [6], Hu, Wu, and Zhu investigated the unstable topological pressure for additive potentials.…”
Section: Introductionmentioning
confidence: 76%
“…Remark 2.9. The definition above appeared in Section 5 of [12], and they showed that C 1 -smooth partially hyperbolic systems enjoy this property, see Theorem D there. In fact, they proved that there is a set C with µ(C) > 0 such that for any…”
Section: Definitions and Preliminariesmentioning
confidence: 98%
See 1 more Smart Citation
“…Some months after the submission of this paper X. Tian and W. Wu made a preprint[16] where they use the expression at the right hand side of Theorem 3.4 to prove several theorems concerning the unstable entropy of non-compact subsets. Although some of the results they obtained are already contained in this paper, their results where stablished following a different approach.…”
mentioning
confidence: 99%